2016
DOI: 10.1111/cge.12740
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent copy number variations as risk factors for autism spectrum disorders: analysis of the clinical implications

Abstract: Chromosomal microarray analysis (CMA) is currently considered a first-tier diagnostic assay for the investigation of autism spectrum disorders (ASD), developmental delay and intellectual disability of unknown etiology. High-resolution arrays were utilized for the identification of copy number variations (CNVs) in 195 ASD patients of Greek origin (126 males, 69 females). CMA resulted in the detection of 65 CNVs, excluding the known polymorphic copy number polymorphisms also found in the Database of Genomic Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 64 publications
1
25
0
1
Order By: Relevance
“…To date, only two interstitial deletion CNVs involving TRIP12 [MIM 604506], encoding a member of the HECT domain E3 ubiquitin ligases family, have been reported in the literature: a de novo ~ 5.4 Mb CNV deletion on 2q36.2q36.3 has been identified in an individual with severe intellectual disability (ID), multiple renal cysts, and dysmorphic features (Doco-Fenzy et al 2008) and a de novo ~ 60 kb deletion involving FBXO36 and the first non-coding exon of TRIP12 has been described in a subject with an autistic spectrum disorder (Pinto et al 2014). An ~ 180 kb CNV duplication encompassing FBXO36 and the 5′ portion of TRIP12 has been reported in an individual with macrocephaly (Figure 1a) (Oikonomakis et al 2016). Recently, four TRIP12 de novo single nucleotide variants have been identified amongst 64 autism spectrum disorders (ASDs) candidate genes re-sequenced in 5,979 individuals; two missense and two truncating variants were detected in individuals with ASDs and ID, ranging from mild to moderate severity (O’Roak et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…To date, only two interstitial deletion CNVs involving TRIP12 [MIM 604506], encoding a member of the HECT domain E3 ubiquitin ligases family, have been reported in the literature: a de novo ~ 5.4 Mb CNV deletion on 2q36.2q36.3 has been identified in an individual with severe intellectual disability (ID), multiple renal cysts, and dysmorphic features (Doco-Fenzy et al 2008) and a de novo ~ 60 kb deletion involving FBXO36 and the first non-coding exon of TRIP12 has been described in a subject with an autistic spectrum disorder (Pinto et al 2014). An ~ 180 kb CNV duplication encompassing FBXO36 and the 5′ portion of TRIP12 has been reported in an individual with macrocephaly (Figure 1a) (Oikonomakis et al 2016). Recently, four TRIP12 de novo single nucleotide variants have been identified amongst 64 autism spectrum disorders (ASDs) candidate genes re-sequenced in 5,979 individuals; two missense and two truncating variants were detected in individuals with ASDs and ID, ranging from mild to moderate severity (O’Roak et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Although it has been estimated that the genetic etiology of ASD may account for up to 40% of cases [ 83 , 84 ] and whole exome sequencing (WES) and chromosomal microarray analysis (CMA) studies have reported yields up to 30% [ 85 ] and 26% [ 86 ], respectively, separate clinical studies have failed to confirm this high rate of genetic disorders in children with ASD. For example, a study from Canada found that 9.3% and 8.4% of children with ASD received a molecular diagnosis using WES and CMA, respectively, resulting in only 15.8% of children with ASD receiving a molecular diagnosis [ 84 ].…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…However, it is difficult to directly compare such diagnostic yields among studies due to the use of different inclusion criteria for diagnostic yields. Some studies report diagnostic yields from only pathogenic CNVs 4 , 8 , 11 , 13 18 , 20 , 22 , 24 , 26 , 28 , 29 , 32 , while others include combined pathogenic CNVs and likely pathogenic CNVs 10 , 23 , 25 , 30 or combined pathogenic CNVs and VOUS 12 , 19 , 21 , 27 . In addition, previous studies have had different inclusion criteria for participating patients and used various microarray platforms with different resolutions.…”
Section: Discussionmentioning
confidence: 99%